The Representative Agent of an Economy with External Habit Formation and Heterogeneous Risk Aversion - Xiouros, Costas; Zapatero, Fernando (Review of Financial Studies, 2010)
In this article, we derive an analytic expression for the representative agent of a large class of economies populated by agents with “catching up with the Joneses” preferences, but who exhibit heterogeneous risk aversion. As Chan and Kogan (2002) show numerically, the representative agent has stochastic risk that moves countercyclically to the state variable. However, we show that heterogeneity of risk aversion alone is insuﬀicient for explaining empirical regularities—namely the variability of the Sharpe ratio—that Campbell and Cochrane (1999) obtain in a model of a representative agent with stochastic risk aversion.